Effect of Blockchain Technology for Sustainable Performance in Supply Chain Management - Wang, Shuang; Tian, Guixian; Islam, Tahir; Khaskhelly, Farhan Zeb; Shaikh, Maria Aijaz (Problemy Ekorozwoju, 2023)
This article discussed the major effect of blockchain technology for sustainable performance in Supply chain management (SCM). Blockchain technology is a technology that performs several operations without letting the information get lost. This digital technology of blockchain will show the potential to reshape the management of supply chain operations in various companies. We will investigate the impact of blockchain technology in relation to efficiency and sustainability. As an example recently the operations in the airport industry have been improving due to technological advances as blockchain technology is handling all the information in the warehouses about product delivery and services in SCM. This technology allows companies to track all types of transactions more securely and transparently and blockchain technology shows benefits, especially in terms of improving Operational Management. The technological disruptions that have an effect on operations must include A-CDM (Airport collaborative decision-making) disruption management and there should be a collaborative network where everyone shares mutual trust and common culture in order to avoid disruption. Airports are still under research in terms of managing blockchain technology efficiently and effectively. The database which is decentralized causes the transactions to be transparent, reliable, traceable, and efficient to supply chain management. This article will be useful to understand the importance of blockchain technology for maintaining sustainability in the operations of SCM along with that we will take an example of SCM in the airport industry to understand how this technology is used there.